Mathematic prediction and experimental research of gas thrust bearing for high-speed turbo-expander involving hydrogen, helium, nitrogen and air working fluids. Issue 1 (1st May 2022) - Yan, H; Zhang, X H; Peng, N; Zheng, L W; Ke, C L; Li, K R; Liang, Y W; Xiong, L Y; Dong, B; Li, J; Liu, I Q
Abstract: High-speed turbo-expander is the key component of large-scale cryogenic liquefaction system and the gas thrust bearing is widely applied in turbo-expander due to the introducing exceptionally low contamination to the gas flow and low viscosity. However, the load capacity of gas bearing is low and it is often difficult to obtain the load capacity because of nonlinear problem. The paper establishes a mathematic prediction model to obtain the load capacity of gas thrust bearing directly and quickly. The model is universal for hydrogen, helium, nitrogen and air working fluids. A new dimensionless variable ( Φ t ) is proposed and the function between the Φ t and load capacity is found. Meanwhile, an experimental study is carried out to validate the mathematic prediction model. The results from the prediction model show good agreement with the experimental data. Based on the model, the load capacity for various working fluids is the same as long as the Φ t is the same, which can be used to conduct experimental research on the replacement of potentially flammable such as hydrogen by inert gas.